Effects of hydroxyapatite coating with oxide interlayer on bioactivity performances in CoCrMo alloy - Mas Ayu, Hassan (2015)
Cobalt-chromium-molybdenum (Co-Cr-Mo) alloys have been reported difficult to bond directly on hard tissues owing to encapsulation by fibrous tissues. Several attempts have been made to improve the situation including coating with a bioactive layer which is mainly hydroxyapatite (HA). Various HA coating methods have been introduced but massive micro crack surface, delamination and low adhesion strength of HA coating are still the major concerns that cause the harmful release of metal ions. In this study, an oxide interlayer on Co-Cr-Mo alloys was developed through thermal oxidation prior to HA coating with the objective to provide better anchorage of HA coatings on the substrate surface, reduce metal ions release and at the same time enhancing the cell attachment. The thermal oxidation process was conducted in a muffle furnace at different temperatures (850°C, 1050°C and 1250°C) for 3 hours to create an oxide interlayer on the substrate surface. It was followed by coating HA on the bare material and on the oxidized substrates using sol gel dip coating technique. Scratch test results showed that the bonding strength of the HA on the oxide interlayer is markedly higher than the HA coated substrates without oxide interlayer. It seems that rough surface of oxide interlayer provides better mechanical interlocking of HA particles to the substrate surface. Inductively coupled plasma-mass spectrometry (ICP-MS) test illustrated that the release of Co and Cr ions from the HA coated oxidized substrates reduced significantly after 28 days immersion as compared to bare material and HA coated substrates without oxide interlayer. This indicates that oxide interlayer is able to act as an additional barrier to suppress the metal ions release. Similarly, the HA coated substrates with oxide interlayer demonstrate strong attachment and proliferation of cells than the HA coated substrates without oxide interlayer. It is concluded that the introduction of an intermediate oxide layer on Co-Cr-Mo substrate prior to HA coating has shown a positive effect in terms of increment of the adhesion strength of HA coating as well as cell bioactivity performance.